Currency Valuations, Retaliation and Trade Conflicts Evidence from Interwar France - Thilo Albers (European Historical Economics Society (EHES), 2017)
The devaluations of the 1930s facilitated a faster recovery from the Great Depression in the countries depreciating, but their unilateral manner provoked retaliatory commercial policies abroad. This paper explores the importance of the retaliatory motive in French trade policy during the 1930s and its effects on trade. Relying on a novel dataset of bilateral tariff rates and a difference in differences approach, the quantification of the protectionist response suggests that retaliation was an important motive behind increasing tariffs. The resulting beggar-my-neighbour penalty reduced trade to a similar degree that modern regional trade agreements foster trade. Furthermore, the analysis of contemporary newspapers reveals that the devaluations of the early 1930s triggered a lasting Anglo-French trade conflict marked by tit-for-tat protectionist policies. Overall, the quantitative and qualitative results indicate that the unilateral currency depreciations came at a high price in political and economic terms.
Keywords: N44; N74; F13; F15; 330; Currency Manipulation; Great Depression; Tariff Retaliation; Beggar-my-neighbour Policies